2003
DOI: 10.1111/j.1346-8138.2003.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Parasites in Patients with Chronic Urticaria

Abstract: Chronic urticaria is an important diagnostic and therapeutic problem. We aimed to investigate the sero-prevalence of tissue parasites causing toxocariasis and fasciolosis in patients with chronic urticaria. All cases were analyzed for antibodies against Toxocara canis and Fasciola hepatica by modified (homemade) ELISA. The excretory/secretory products of Toxocara and Fasciola were used as antigens (ES-ELISA) in the test. In this study, the highest toxocariasis seropositivity (29.0%) rate and the highest fascio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 11 publications
0
28
0
4
Order By: Relevance
“…Bizim çalışmamızda da literatürle benzer şekilde hastaların %50 kadarında OSDT pozitifliği saptanmıştır. KÜ ile paraziter infeksiyonlar arasında açık bir ilişki saptanmamış olup sadece küçük vaka serilerinde Blastocystis hominis, Toxocara canis, Giardia lamblia, Strongyloides stercoralis ile KÜ arasında ilişki olduğu ifade edilmiştir 4,29 . Ancak KÜ'de remisyon açısından dışkıda parazit saptanarak antiparaziter tedavi alan ve dışkıda parazit saptanmayan grup arasında anlamlı farklılık olmadığı görülmüştür 16 .…”
Section: Discussionunclassified
“…Bizim çalışmamızda da literatürle benzer şekilde hastaların %50 kadarında OSDT pozitifliği saptanmıştır. KÜ ile paraziter infeksiyonlar arasında açık bir ilişki saptanmamış olup sadece küçük vaka serilerinde Blastocystis hominis, Toxocara canis, Giardia lamblia, Strongyloides stercoralis ile KÜ arasında ilişki olduğu ifade edilmiştir 4,29 . Ancak KÜ'de remisyon açısından dışkıda parazit saptanarak antiparaziter tedavi alan ve dışkıda parazit saptanmayan grup arasında anlamlı farklılık olmadığı görülmüştür 16 .…”
Section: Discussionunclassified
“…1,4,5,27 In a study carried out in a dermatologic population, Wolfrom et al 1,27 found that 65% of patients with chronic urticaria had anti-Toxocara antibodies (Table III). This association was highly significant (P\.0001).…”
Section: Chronic Urticariamentioning
confidence: 93%
“…Other cutaneous manifestations associated with toxocariasis such as chronic pruritus, chronic prurigo, miscellaneous eczema, panniculitis, and vasculitis have also been observed. [1][2][3][4][5] In some cases, dermatologic symptoms were the only signs indicating the presence of the disease. 6,7 When dermatologists examine a patient with cutaneous lesions (regardless of the presence or absence of blood hypereosinophilia), that have been recurring for several months or years, and for which Toxocara canis excretory-secretory VLM: visceral larva migrans no origin has been found despite repeated clinical examinations and investigations, they should think of toxocariasis, given its high prevalence throughout the world.…”
mentioning
confidence: 99%
“…Eine Studie aus der südwestlichen Türkei ergab bei 9 von 62 (14,5%) Patienten mit Urtikaria Antikörper gegen Fasciola hepatica, wäh-rend dies nur bei 1 von 62 (1,6%) gesunden Kontrollen der Fall war. Allerdings ist unklar, ob zum Zeitpunkt des Auftretens der Urtikaria tatsächlich eine akute Infektion mit Fasciola vorlag [8].…”
Section: Fascioloseunclassified
“…Bei der Suche nach Auslösern einer Urtikaria wird in Regionen, in denen parasitäre Erkrankungen nur selten vorkommen, oft übersehen, dass sowohl intestinale als auch Gewebsparasiten akute oder chronische Urtikaria verursachen kön-nen [8]. Erschwerend kommt hinzu, dass v. a. intestinale Parasiten manchmal wenige oder keine weiteren Krankheitssymptome verursachen.…”
unclassified